Identification of hub fatty acid metabolism-related genes and immune infiltration in IgA nephropathy - Xiaoqian Qian; Shuyang Bian; Qin Guo; Dongdong Zhu; Fan Bian; Yinhui Song; Gengru Jiang (Renal Failure)
Aims To investigate the potential mechanisms of fatty acid metabolism (FAM)-related genes in IgA nephropathy (IgAN) and to explore its immune cell infiltration characteristic.Methods Datasets for IgAN and FAM-related genes were obtained from GEO and MSigDB database, respectively. We employed differential expression analysis and WGCNA to identify common genes. GO and KEGG analyses were performed to compare the differences between IgAN and control groups. Furthermore, LASSO logistic regression was applied to develop a predictive model based on FAM-related genes. The efficacy of this prognostic model was evaluated using ROC analysis. The infiltration of immune cells and immune-related functions were assessed with CIBERSORT tool. Finally, the identified key genes were validated in blood samples from IgAN and control patients, as well as in human mesangial cells (HMCs) following Gd-IgA stimulation using Real-time PCR.Results A total of 12 hub genes linked to FAM were identified in patients with IgAN. A predictive model consisting of four genes was conducted through COX and LASSO regression analysis, revealing AUC values that indicate a relatively strong diagnostic capability. Immune infiltration analysis indicated that various immune cells have significant associations with IgAN. Additionally, Real-time PCR assays confirmed that the expression levels of hub genes were markedly reduced in IgAN patients and in Gd-IgA treated HMCs compared to controls.Conclusion This study employed bioinformatics methods to unveiled the immune cell infiltration associated with IgAN and to explore the potential genetic connection between FAM and IgAN. This could aid in predicting the risk of IgAN and enhance both diagnosis and prognosis of this condition.